STRATEGI LIVELIHOOD BERKELANJUTAN MASYARAKAT PADA WILAYAH MULTIHAZARD DI DAS SENGKARANG, KABUPATEN PEKALONGAN - Rita Noviani; Aulia Indri; Salsabila Atha; Syahwa Naila; Nina Marlina; Salsa Sabila Ulfa; Alya Aulia; Annisaul Hanifah; Farid Abduh; Muhammad Farrell (JURNAL ILMIAH NUSANTARA, 2026)
The Sengkarang Watershed in Pekalongan Regency is a multihazard area facing landslide threats in the upstream zone, flooding in the midstream zone, and tidal flooding (rob) in the downstream zone, directly affecting the livelihoods of local communities. This study aims to identify the condition of Livelihood assets, analyze Livelihood strategies, and describe strategy differences across zones using the DFID Sustainable Livelihood Approach (SLA) framework. The research was conducted in six villages within Tirto and Petungkriyono Districts, involving 97 respondents distributed across the flood zone (n=45), tidal-flood zone (n=40), and landslide zone (n=12). A mixed-method approach was applied, combining quantitative scoring and asset-pentagon indices, qualitative in-depth interviews, and simple spatial analysis using ArcGIS. The results show an overall mean Livelihood index of 0.3476 (Medium category), with physical capital as the strongest asset (0.5021) and financial capital as the weakest (0.2541). The landslide zone recorded the highest index (0.4817), driven by a very high natural capital value (0.7917), while the tidal-flood zone recorded the lowest index (0.3143) due to extremely low natural capital (0.1396). Community Livelihood strategies include job diversification, Livelihood adaptation, coping mechanisms, and informal social network mobilization, each varying in intensity across hazard zones. This study recommends zone-specific, cross-sectoral interventions to strengthen financial and social capital across all zones, natural capital in flood and tidal-flood zones, and accessibility in the landslide zone.